GET WITH THE BEAT! THE REGULATION OF UNDERWATER NOISE IN SOUTH AFRICA - Adelaide Karomo; Stephanie Plön; Patrick Vrancken (Obiter, 2023)
Anthropogenic noise in the oceans, including from shipping and seismic surveys, is of concern as it often adversely impacts marine life and biodiversity. It is considered to be the number-one ocean pollutant today. The authors review major international legal instruments regarding underwater noise as a marine pollutant and examine them in the South African context. The authors find, inter alia, that a distinction between substance-based pollution (such as chemical pollution) and energy-based pollution (such as noise) is currently lacking. It is also found that very little literature is available on the impacts of shipping and seismic noise on small fish, turtles and cetaceans, a state of affairs that calls for a precautionary approach. It is recommended: (1) South African legal instruments that regulate underwater noise should be revised and aligned with international legal frameworks; (2) more scientific research should be conducted on the cumulative impacts of shipping and seismic surveys on the South African marine environment; and (3) the public participation process should be effectively monitored to ensure full compliance with the requirement to consult all affected and interested persons. Doing so would have wider implications for developments in the western Indian Ocean region regarding shipping, port construction and seismic explorations.